Pengaruh Produk Domestik Regional Bruto dan Indeks Pembangunan Manusia Terhadap Tingkat Pengangguran Terbuka di Provinsi Sumatera Barat - M Arizal; Marwan Marwan (Jurnal Ecogen, 2019)
This research aimed to know how the effect of Gross Regional Domestic Bruto and Human Devolopment Indeks (HDI) toward open unemployment rate in West Sumatera with selected model is the Fixed Effect Model (FEM) The data were used panel data during the period 2010-2017, with the technique of collecting documentation data and library studies obtained  from relevant institusions and agencies. The independent variables of this study are Gross Regional Domestic Bruto (X1) and Human Devolopment Indeks r (X2). The research method used is Odinary Least Square (OLS) that use classical Assumtions, determination coeffisient test (R2), and hypothesis test used t-test with significance level of 5%.. The estimation results show that, gross regional domestic product have a negative and significant effect on open unemployment rate in West Sumatera, and Human Development Indeks have a positive and significant effect on open unemployment in West Sumatera. Meanwhile simultaneously Gross Regional Domestic Bruto and Human Devolopment Indeks affect the open unemployment rate in West Sumatera. Keyword:  open unemplument, human development indeks, gross domestic product and ordinary keast square (ols)